2020
DOI: 10.1002/jimd.12323
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular characterization of adult patients with late‐onset MTHFR deficiency

Abstract: 5,10‐Methylenetetrahydrofolate reductase (MTHFR) deficiency usually presents as a severe neonatal disease. This study aimed to characterize natural history, biological and molecular data, and response to treatment of patients with late‐onset MTHFR deficiency. The patients were identified through the European Network and Registry for Homocystinuria and Methylation Defects and the Adult group of the French Society for Inherited Metabolic Diseases; data were retrospectively colleted. To identify juvenile to adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Though previous studies already reported clinical data on MTHFR-deficient patients, these studies either included late-onset MTHFR deficiency or did not focus on neurodevelopmental outcomes. 23,28 Huemer et al 25 analysed the clinical presentation of 50 MTHFR-deficient patients. Forty-three of these previously reported patients (including two with pre-symptomatic diagnosis) were included into our study, which, in contrast to the earlier publication focused on early-onset presentation and neurodevelopmental outcomes of MTHFR-deficient patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though previous studies already reported clinical data on MTHFR-deficient patients, these studies either included late-onset MTHFR deficiency or did not focus on neurodevelopmental outcomes. 23,28 Huemer et al 25 analysed the clinical presentation of 50 MTHFR-deficient patients. Forty-three of these previously reported patients (including two with pre-symptomatic diagnosis) were included into our study, which, in contrast to the earlier publication focused on early-onset presentation and neurodevelopmental outcomes of MTHFR-deficient patients.…”
Section: Discussionmentioning
confidence: 99%
“…Though previous studies already reported clinical data on MTHFR‐deficient patients, these studies either included late‐onset MTHFR deficiency or did not focus on neurodevelopmental outcomes 23,28 . Huemer et al 25 analysed the clinical presentation of 50 MTHFR‐deficient patients.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical spectrum of the disease is heterogeneous. There are many neurological manifestations associated with the syndrome, like cognitive decline, behavioral abnormalities, seizures, gait disorders, encephalopathy, thrombotic events, myasthenia, motor disorders and paresthesias [1,2]. Hyperhomocysteinemia type II is due to MTHFR gene mutation.…”
Section: Discussionmentioning
confidence: 99%